PEMBERDAYAAN MASYARAKAT UNTUK MENINGKATKAN KESIAPSIAGAAN MENGHADAPI PANDEMI COVID 19 DI DESA WAY MULI TIMUR KECAMATAN RAJABASA KABUPATEN LAMPUNG SELATAN - Dwi Agustanti Pohan; Purbianto . (ABDIKEMAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
Lampung Province, Covid 19 cases, on March 18 - April 24 2020, there were 64 PDP cases, 38 positive, 10 recovered and 5 died (TVRI Lampung, 24 April 2020). Rajabasa Puskesmas Lampung Selatan, 3 ODP people and there have been no positive cases, but public knowledge about the spread of Covid 19 is still low. The aim of the activity is to increase public knowledge and skills about Covid 19 and PHBS to prevent the transmission and spread of Covid 19 with 3M principles. The implementation of the program from September to November 2020 can go according to plan, namely the Health Center on Covid 19, training how to wash hands in 6 correct steps, distributing masks and hand sanitizers to the public and health workers at the Rajabasa Community Health Center and strengthening physical endurance by distributing groceries to 30 families that was affected by the tsunami as well as Covid 19. The results of the activity were increased public knowledge about Covid 19, increased PHBS, increased physical resilience, the commitment of the Covid 19 Village Task Force to motivate and monitor PHBS, especially 3M behavior. In the final evaluation, the Covid 19 case was confirmed to be positive "Nil".